Non-pharmacological interventions for the reduction and maintenance of blood pressure in people with prehypertension: a systematic review protocol - Paul Rutter; Andrew Clegg; Valerio Benedetto; Caroline Watkins; Nefyn Williams; Joseph Spencer; Lucy Hives; Emma P Bray; Cath Harris; Rachel F Georgiou; Nafisa Iqbal (BMJ Open)
Introduction Prehypertension is defined as blood pressure that is above the normal range but not high enough to be classed as hypertension. Prehypertension is a warning of development of hypertension as well as a risk for cardiovascular disease, heart attack and stroke. In the UK, non-pharmacological interventions are recommended for prehypertension management but no reviews have focused on the effectiveness of these types of interventions solely in people with prehypertension. Therefore, the proposed systematic review will assess the clinical effectiveness and cost-effectiveness of non-pharmacological interventions in reducing or maintaining blood pressure in prehypertensive people.Methods and analysis This systematic review will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The databases/trial registries that will be searched to identify relevant randomised controlled trials (RCTs) and economic evaluations include Medline, EMBASE, CINAHL, PsycINFO, CENTRAL, the WHO International Clinical Trials Registry Platform, ClinicalTrials.gov, Cochrane Library, Scopus and the International HTA Database. Search terms have been identified by the team including an information specialist. Three reviewers will be involved in the study selection process. Risk of bias will be evaluated using the Cochrane risk-of-bias tool for RCTs and the Consensus Health Economic Criteria list for economic evaluations. Findings from the included studies will be tabulated and synthesised narratively. Heterogeneity will be assessed through visual inspection of forest plots and the calculation of the χ2 and I2 statistics and causes of heterogeneity will be assessed where sufficient data are available. If possible, we plan to investigate differential effects on specific subgroups and from different types of interventions using meta-regression. Where relevant, the Grading of Recommendations, Assessment, Development and Evaluations (GRADE) will be used to assess the certainty of the evidence found.Ethics and dissemination Ethical approval is not needed. Results will be published in a peer-reviewed journal, disseminated via the wider study website and shared with the study sites and participants.Registration details The review is registered with PROSPERO (CRD420232433047).